2022
DOI: 10.3390/vaccines10060840
|View full text |Cite
|
Sign up to set email alerts
|

Leaving No One Behind: Interventions and Outcomes of the COVID-19 Vaccine Maximising Uptake Programme

Abstract: The devastating impact of COVID-19 on individuals and communities has accelerated the development of vaccines and the deployment of ambitious vaccination programmes to reduce the risks of infection, infection transmission and symptom severity. However, many people delay or refuse to get vaccinated against COVID-19, for many complex reasons. Vaccination programmes that are tailored to address individual and communities’ COVID-19 concerns can improve vaccine uptake rates and help achieve the required herd-immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Previous literature highlights gaps in understanding around how to develop tailored and targeted health interventions involving migrants, beyond engaging with community‐based organisations and using culturally appropriate messaging 49 . There are also limited examples of participatory, co‐designed vaccination interventions involving migrant populations 50–55 . Our study addresses this gap and offers a valuable example of a community‐engaged approach to co‐designing a vaccination intervention for an underserved migrant community.…”
Section: Discussionmentioning
confidence: 93%
“…Previous literature highlights gaps in understanding around how to develop tailored and targeted health interventions involving migrants, beyond engaging with community‐based organisations and using culturally appropriate messaging 49 . There are also limited examples of participatory, co‐designed vaccination interventions involving migrant populations 50–55 . Our study addresses this gap and offers a valuable example of a community‐engaged approach to co‐designing a vaccination intervention for an underserved migrant community.…”
Section: Discussionmentioning
confidence: 93%
“…Several contextualized models in the health literature have also enhanced vaccine uptake among similar underserved populations. Such vaccination models employed multipronged strategies similar to those used in Calgary, including intersectoral collaboration, translated communication through the right channels, building trust, and performing outreach [ 26 , 27 , 29 , 36 ]. Only one model in the literature considered the integration of community partner input in policy, planning and decision making, as was found in Calgary area newcomer refugee and immigrant vaccination models [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2003, various vaccination models for newcomer refugee and immigrant populations have been reported in the health literature, primarily from the United States ( n = 17) (Aghajafari, Guzek, Kamal, et al: A scoping review of COVID-19 vaccination models for refugees, unpublished) with only two studies conducted in Canada [ 22 , 23 ]. Vaccination models range in intervention scope and components – including wide-scale information campaigns [ 24 , 25 ], mobile outreach programs [ 21 , 22 , 26 , 27 ], and community vaccination sites [ 28 , 29 ]. Most vaccination models incorporate multiple elements including vaccine promotion, coordination, and vaccine delivery, and some incorporate language translation (Aghajafari, et al: A scoping review of COVID-19 vaccination models for refugees, unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…Our study ndings also revealed that mobile health workers hold the perception that their engagement as extra hands to support xed health workers (i.e., health workers domiciled in the facilities), signi cantly in uenced the optimization of COVID-19 vaccination in Benue and Niger states because they were actively engaged in reaching the nooks and crannies of their local government areas to address misconceptions about COVID-19 and educate community residents on the bene ts of taking COVID-19 vaccines whilst they are also getting people vaccinated. This claim alludes to the outcomes of "The Maximizing Uptake Programme" (Berrou et al, 2022) in the Southwest of England, where outreach service was used to vaccinate underserved populations such as homeless people, refugees, and asylum seekers who are highly susceptible to COVID-19 and/or have limited access to vaccination centers. The perception held by the teams may be based on the possibility of observing a high level of hesitancy among community residents, particularly residents domiciled in underserved communities of the various…”
Section: Discussionmentioning
confidence: 99%